A internacionalização da universidade empreendedora: a proposta de um modelo - Ferreira, Jeferson Vinhas (2017)
This thesis aims to develop a conceptual model for the analysis of the internationalization process of an entrepreneurial university. Globalization has demanded from all worldwide competitive organizations a cross-border looking, which necessarily goes through internationalization processes. In this competitive scenario, it was arisen the concept of the entrepreneurial universities, which seek to face the current economic challenges through the practice of entrepreneurship. One of the alternatives for that challenge is higher education internationalization. Based on this context, it was conducted a multi-case study involving nine entrepreneurial higher education institutions (HEI’s) from seven countries of Latin America and Europe which are members of a cooperation network. Data collection was done by interviewing the leaders of those HEI’s, as well as by conducting a documentary survey and direct observation. Data analysis implicated the triangulation of such information with the support of qualitative analysis software (NVivo). The given conceptual model pinpointed six essential internationalization process elements of the entrepreneurial universities: internationalization as a strategic pillar, entrepreneurial capacity of the leaders, a culture of integrated internationalization, reciprocities practices among institutional partners, concerning about parity in these partnerships, and, finally, approaching to the industry. As result of this study, five propositions were suggested in order to compose the conceptual model to be used in future researches